2017
DOI: 10.2147/ijn.s137833
|View full text |Cite
|
Sign up to set email alerts
|

Targeting integrins with RGD-conjugated gold nanoparticles in radiotherapy decreases the invasive activity of breast cancer cells

Abstract: Gold nanoparticles (AuNPs) have recently attracted attention as clinical agents for enhancing the effect of radiotherapy in various cancers. Although radiotherapy is a standard treatment for cancers, invasive recurrence and metastasis are significant clinical problems. Several studies have suggested that radiation promotes the invasion of cancer cells by activating molecular mechanisms involving integrin and fibronectin (FN). In this study, polyethylene-glycolylated AuNPs (P-AuNPs) were conjugated with Arg–Gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 68 publications
1
74
0
2
Order By: Relevance
“…Another problem is the localization of AuNPs in cells. As described above, integrin-targeted NPs mainly accumulate in late endosomes and lysosomes [78]. This localization suggests that NPs appear to work in lysosomes, but in some situations, the function of the lysosomes might decrease NP efficacy.…”
Section: Issues Of Integrin-targeted Npsmentioning
confidence: 71%
See 4 more Smart Citations
“…Another problem is the localization of AuNPs in cells. As described above, integrin-targeted NPs mainly accumulate in late endosomes and lysosomes [78]. This localization suggests that NPs appear to work in lysosomes, but in some situations, the function of the lysosomes might decrease NP efficacy.…”
Section: Issues Of Integrin-targeted Npsmentioning
confidence: 71%
“…These characteristics have inspired individuals to conjugate integrin-targeted ligands to the surface of AuNPs, which illustrates the concept of "targeted radiosensitizers". We have reported the radiosensitizing effects of RGD-conjugated polyethylene-glycosylated AuNPs (RGD/P-AuNPs) on integrin-overexpressing breast cancer cells [78]. Our study showed that RGD/P-AuNPs are efficaciously internalized into integrin-overexpressing cancer cells subjected to an increase in radiation-induced DNA damage.…”
Section: Radiotherapymentioning
confidence: 83%
See 3 more Smart Citations